Induction of islet autoimmunity to defective ribosomal product of the insulin gene as neoantigen after anti-cancer immunotherapy leading to autoimmune diabetes - van Tienhoven, Rene; Jansen, Diahann T. S. L.; Park, Miso; Williams, John C.; Larkin, James; Quezada, Sergio A.; Roep, Bart O. (Frontiers in Immunology, 2024)
The autoimmune response in type 1 diabetes (T1D), in which the beta cells expressing aberrant or modified proteins are killed, resembles an effective antitumor response. Defective ribosomal protein products in tumors are targets of the anti-tumor immune response that is unleashed by immune checkpoint inhibitor (ICI) treatment in cancer patients. We recently described a defective ribosomal product of the insulin gene (INS-DRiP) that is expressed in stressed beta cells and targeted by diabetogenic T cells. T1D patient-derived INS-DRiP specific T cells can kill beta cells and are present in the insulitic lesion. T cells reactive to INS-DRiP epitopes are part of the normal T cell repertoire and are believed to be kept in check by immune regulation without causing autoimmunity. Here we report the induction of islet autoimmunity to INS-DRiP and diabetes after ICI treatment and successful tumor remission. Following ICI treatment, T cells of the cancer patient were primed against INS-DRiP among other diabetogenic antigens, while there was no sign of autoimmunity to this neoantigen before ICI treatment. Next, we demonstrated the expression of INS-DRiP as neoantigen in both pancreatic islets and insulinoma by staining with a monoclonal antibody to INS-DRiP. These results bridge cancer and T1D as two sides of the same coin and point to neoantigen expression in normal islets and insulinoma that may serve as target of both islet autoimmunity and tumor-related autoimmunity.